(untitled) (Research, Society and Development, 2020)
There is a constant search for drugs to fight infections effectively. Herbal medicines are presented as options that, in addition to having great therapeutic potential, generally have low cost. Literature data show that rosemary (Rosmarinus officinalis) has antimicrobial activity. Thus, the objective of this work was, through the existing literature, to verify whether R. officinalis has therapeutic and antimicrobial properties in pathological conditions of the oral cavity, and can be used for treatments of mouth infections. In the present review, the databases used for screening were: Scientific Eletronic Library Online (SCIELO) and PubMED, using the following descriptors: "Rosemary" "Rosmarinus officinalis", "Antimicrobial action", "application in Dentistry", “Phytotherapy in Dentistry”, isolated or in combination, in Portuguese and English. The studies were analyzed according to the year of publication, publication period and results found. Among the researches evaluated, only 3 did not show significant results regarding their antimicrobial action. In other studies, it was found to be effective against fungi, bacteria, viral agents and to inhibit the formation of oral biofilms. Thus, the literature points to the effectiveness of R. officinalis as an antimicrobial in relation to fungi and pathogenic bacteria in the mouth, having a clinical application in the treatment and prevention of diseases of the oral cavity.